HASIL BELAJAR KOGNITIF MENGGUNAKAN MODEL PEMBELAJARAN READING CONCEPT MAP COOPERATIVE SCRIPT (REMAP-CS) DAN READING CONCEPT MAP TIMED PAIR SHARE (REMAP-TMPS) - Idawati Mansyur; Ainul Uyuni Taufiq; Safei Safei (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
This study determined the comparison of student learning outcomes between the application of the Reading Concept Map Cooperative Script (ReMap-CS) learning model and the Reading Concept Map Timed Pair Share (ReMap-TmPS). This type of study was quasi-experimental using the pretest-posttest nonequivalent control group design. The research population is all students of class XI IPA SMAN 2 Gowa as many as 323 students. The research sample consisted of 24 students of class XI IPA 6 and 24 students of class XI IPA 7 selected by the purposive sampling technique. The learning outcomes research instruments were learning outcomes tests in the form of questions and assignments regarding the excretory system material used to measure student competency achievement. The data analysis technique used was descriptive data analysis and inferential data analysis. The results showed that the average student learning outcomes using the ReMap-CS learning model were 83,33 while the ReMap-TmPS learning model was 78,33. The t-test results show that the sig (2-tailed) value is 0,008. Results indicate that the sig. (2-tailed) value <0.05, which means a significant difference between learning outcomes in both the experimental class 1 and the experimental class 2, where experimental class 1 using Remap-CS is better than experiment 2 using ReMap-TmPs